Long-term follow-up after epilepsy surgery in infancy and early childhood – A prospective population based observational study. (August 2015) - Reinholdson, Jesper; Olsson, Ingrid; Edelvik, Anna; Hallböök, Tove; Lundgren, Johan; Rydenhag, Bertil; Malmgren, Kristina
Highlights: This is a prospective, population based, longitudinal study. A favourable seizure outcome is consistent over time in the majority of cases. Many children can stop taking antiepileptic drugs. Early referral of young children with medically intractable epilepsy is important. Abstract: Purpose: To describe 2-year and long-term outcomes (five or ten years) after resective epilepsy surgery in children operated before the age of four years. Methods: This prospective, population based, longitudinal study is based on data from the Swedish National Epilepsy Surgery Register 1995–2010. The following variables were analysed: seizure frequency, antiepileptic drug treatment (AED), neurological deficits, type of operation, histopathological diagnosis and perioperative complications. Results: During the study period 47 children under four years had resective surgery. A majority had seizure onset within the first year of life, and the median age at surgery was two years and one month. Two thirds had neurodevelopmental abnormalities. Temporal lobe resection, frontal lobe resection and hemispherotomy predominated. A majority had malformations of cortical development. There was one major perioperative complication. At the 2-year follow-up, 21/47 children (45%) were seizure free, eight of whom were off medication. At the long-term follow-up, 16/32 (50%) were seizure-free and 11 of them off medication. Another ten (31%) had ≥75% reduction in seizure frequency. Fourteen children (44%) had sustained seizure freedom from surgery to the long-term follow-up. Conclusion: This is the first prospective, population based, longitudinal study to show that a favourable seizure outcome is achievable in a majority of infants and young children undergoing resective epilepsy surgery and that the improvements are consistent over time. Many can also stop taking AEDs. The findings emphasise the importance of early referral to epilepsy surgery evaluation in cases of medically intractable epilepsy in infants and young children.